High Areal Capacitance of N‐Doped Graphene Synthesized by Arc Discharge. (19th September 2019) - Pham, Thang Viet; Kim, Jeong‐Gil; Jung, Jae Young; Kim, Jun Hee; Cho, Hyunjin; Seo, Tae Hoon; Lee, Hunsu; Kim, Nam Dong; Kim, Myung Jong
Abstract: The lack of cost effective, industrial‐scale production methods hinders the widespread applications of graphene materials. In spite of its applicability in the mass production of graphene flakes, arc discharge has not received considerable attention because of its inability to control the synthesis and heteroatom doping. In this study, a facile approach is proposed for improving doping efficiency in N‐doped graphene synthesis through arc discharge by utilizing anodic carbon fillers. Compared to the N‐doped graphene (1–1.5% N) synthesized via the arc process according to previous literature, the resulting graphene flakes show a remarkably increased doping level (≈3.5% N) with noticeable graphitic N enrichment, which is rarely achieved by the conventional process, while simultaneously retaining high turbostratic crystallinity. The electrolyte ion storage of synthesized materials is examined in which synthesized N‐doped graphene material exhibits a remarkable area normalized capacitance of 63 µF cm −2 . The surprisingly high areal capacitance, which is superior to that of most carbon materials, is attributed to the synergistic effect of extrinsic pseudocapacitance, high crystallinity, and abundance of exposed graphene edges. These results highlight the great potentials of N‐doped graphene flakes produced by arc discharge in graphene‐based supercapacitors, along with well‐studied active exfoliated graphene and reduced graphene oxide. Abstract : The nitrogen doping efficiency of graphene synthesis via arc discharge has noticeably improved (up to ≈3.5%, and notable amount of graphitic N) by utilizing anodic carbon fillers. The obtained N‐doped graphene exhibits a remarkably high areal capacitance of 63 µF cm −2 ascribed to extrinsic pseudocapacitance, modified quantum and space charge capacitance arising from nitrogen doping, and the abundance of exposed graphene edges.